Preparation method of carbon-supported core-shell structure platinum-copper alloy catalyst for fuel cell

By preparing the carbon -load nuclear shell structure of the platinum and copper alloy catalyst in the aquare, the problem of low platinum resource utilization and poor catalyst stability in existing technologies has been solved.

CN119381462APending Publication Date: 2025-01-28CENT SOUTH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411512175.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Among the existing proton exchange membrane fuel cell catalysts, the platinum resource utilization rate is low, and the transition metal elements are easily dissolved under high potential, resulting in the collapse of the catalyst structure and the reduction of activity, and the preparation process is complex and the cost is high.

Method used

The preparation method of carbon -loading nano -copper is used, and a platinum copper alloy catalyst is prepared in the aqueous solution. The nuclear shell structure and coordination effect are used to improve the utilization rate of platinum and the stability of the catalyst.

Benefits of technology

It improves the utilization of platinum, reduces the cost of catalytic preparation, significantly improves the electrochemical properties and durability of the catalyst, and the quality activity can reach 0.9A · MGPT-1 and above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381462A_ABST
    Figure CN119381462A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon-supported core-shell structure platinum-copper alloy catalyst for a fuel cell, and belongs to the field of fuel cells. The preparation method comprises the following steps: fully dipping a carbon carrier in a copper-containing solution, adding sodium hydroxide to adjust the pH value of the solution, and then adding a reducing agent for full reduction to obtain carbon-loaded nano-copper particles; and after the carbon-supported nano-copper particles are fully soaked in a platinum nitrate solution, the mixed solution is transferred into a reaction kettle, then a certain mass of a coordination agent is added into the solution, the temperature is increased to 70-110 DEG C, hydrogen is introduced for pressurized hydrogen reduction, and the carbon-supported core-shell structure platinum-copper alloy catalyst is obtained. The mass activity of the carbon-supported core-shell structure platinum-copper alloy catalyst synthesized by two steps in a water phase system is higher than 0.9 A.mgPt <-1 >, and is superior to the mass activity of a mainstream platinum-carbon catalyst in the current market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fuel cells, and in particular to a method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for fuel cells. Background Art

[0002] After the first industrial revolution, fossil energy began to be widely used in human social activities. At that time, the world population was only about 700 million. Today, more than 200 years later, the world population has soared to 7 billion, and it is expected that the world population will exceed 10 billion in 2050. With the rapid growth of the world population, the demand for energy will further expand. The combustion of traditional fossil energy will produce a large amount of greenhouse gases, causing the melting of polar glaciers and the rise of sea levels, posing a huge threat to the future survival of mankind. Therefore, it is crucial to reduce the use of fossil fuels and reduce greenhouse gas emissions.

[0003] The proton exchange membrane fuel cell is a device that directly converts the chemical energy of hydrogen into electrical energy. It is not limited by the Carnot cycle, and its energy conversion efficiency is 2 to 3 times that of a traditional internal combustion engine. It uses a solid Nafion membrane as an electrolyte, is small in size and easy to carry, and is an energy device with good application prospects. The catalyst currently used in proton exchange membrane fuel cells is a platinum-carbon catalyst. The uneven distribution of platinum resources, small reserves, and high prices have greatly restricted the development and application of proton exchange membrane fuel cells. In the 1980s, scientists discovered that the alloying of platinum with transition metals, the coordination effect and stress effect between transition metals and platinum, can improve the activity of the catalyst. Since then, platinum alloy catalysts have begun to enter people's field of vision.

[0004] Platinum alloy catalysts have improved the utilization rate of platinum to a certain extent, but there is still a large amount of platinum buried in the bulk phase, resulting in a waste of platinum resources. The transition metal elements exposed on the surface have low redox potentials and are easily dissolved under high potentials, causing the catalyst structure to collapse and activity to decrease. In view of the shortcomings of the alloy structure, people have proposed a core-shell structure, which increases the exposure of platinum on the surface while utilizing the coordination effect and stress effect, and reduces the dissolution of transition metal elements. At present, the preparation of high-quality active platinum alloy catalysts relies on the solvothermal method, which has a long preparation time, small scale, and high cost, which is not conducive to industrial application. (Gong M, Deng Z, Xiao D, ect. One-Nanometer-Thick Pt 3Ni BimetallicAlloy Nanowires Advanced Oxygen Reduction Reaction: Integrating Multiple Advantages into One Catalyst. ACS Catal, 2019, 9(5): 4488~4494)(Xu Shen, Gong Jingjing, Shi Yingfei. Research on the preparation of platinum-carbon catalyst for proton exchange membrane fuel cells by ethylene glycol method. Battery Industry, 2023, 27(2): 55-60+73)(Gu J, Zhang GM, Yao R, et al. High Oxygen Reduction Activity of Pt-Ni AlloyCatalyst for Proton Exchange Membrane Fuel Cells. Catalysts, 2022, 12(3): 250) Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing a carbon-supported core-shell platinum-copper alloy catalyst for fuel cells with excellent electrochemical performance. The specific process is as follows:

[0006] A. Preparation of Carbon-supported Nanocopper

[0007] The copper salt is completely dissolved in pure water, and the concentration of copper in the solution is controlled to be 0.1-1.5 g / L. A carbon carrier is then added to the above solution, and the ratio of the mass of the carbon carrier to the mass of copper is controlled to be 1.5-4.6:1. After stirring and impregnating for 3-6 hours, a copper-containing precursor mixed solution is obtained.

[0008] A sodium hydroxide solution with a concentration of 15 to 20 g / L is added dropwise to a mixed solution containing a copper precursor, the pH of the mixed solution is adjusted to 9 to 13, a reducing agent is added according to a mass ratio of the reducing agent to copper in the mixed solution of 0.8 to 2.5:1, the temperature is increased to 50 to 70°C, the reaction is carried out for 15 to 75 minutes, and the mixture is filtered and dried to obtain carbon-supported nano-copper particles.

[0009] B. Preparation of Carbon-Supported Platinum-Copper Alloy Catalyst

[0010] A platinum solution with a platinum concentration of 0.45 to 1.75 g / L is prepared, and a sodium hydroxide solution with a concentration of 20 to 40 g / L is used to adjust the pH of the platinum solution to 2.0 to 8.0, and then the carbon-supported nano-copper particles are added to the platinum solution to obtain a platinum-containing mixed solution, and the molar ratio of Cu and Pt in the platinum-containing mixed solution is controlled to be 1 to 3:1, and the mixture is stirred and impregnated for 3 to 11 hours. The platinum-containing mixed solution is placed in a reactor, and a ligand is added to the mixed solution, and the concentration of the ligand in the solution is controlled to be 0.1 g / L to 1.5 g / L, and the pH of the platinum-containing mixed solution is adjusted to 2.0 to 8.0 using a sodium hydroxide solution with a concentration of 20 to 40 g / L. The reaction mixture was adjusted to 5.0-8.0; then, argon was introduced into the reactor to drive out all the oxygen in the reactor, and the temperature was raised to 70-110° C., and hydrogen was introduced into the reactor to control the hydrogen partial pressure in the reactor to be 0.45-1.0 MPa, and the solution was stirred at a rate of 150-350 rpm for 60-120 min, and then the heating and stirring were stopped. When the temperature in the reactor dropped below 50° C., the introduction of hydrogen was stopped and argon was introduced into the reactor to replace the hydrogen. When the hydrogen was completely replaced, the solid-liquid separation was carried out, and the catalyst was washed with ethanol and dried to obtain a carbon-supported core-shell structured platinum-copper alloy catalyst.

[0011] The platinum salt is platinum nitrate; the copper salt is at least one of copper nitrate trihydrate and copper sulfate pentahydrate; the carbon carrier is at least one of ECP600JD, EC600JD, and XC-72; the reducing agent is hydrazine hydrate; the coordination agent is at least one of sodium nitrite and EDTA-2Na; the purity of the hydrogen is not less than 99.99%; the purity of the argon is not less than 99.99%.

[0012] Compared with the prior art, the present invention has the following beneficial effects: the carbon-supported core-shell structure platinum-copper alloy catalyst prepared by the present invention has a higher utilization rate of platinum than the popular platinum-carbon catalyst on the market, and can achieve partial replacement of platinum in the popular platinum-carbon catalyst on the market, thereby reducing the cost of catalyst preparation; the preparation process of the present invention is completely carried out in an aqueous solution, and the preparation process is simple and the cost is low; the present invention realizes the coating of platinum on copper, increases the stability and durability of the catalyst, and the electrochemical performance is significantly better than the popular platinum-carbon catalyst on the market, and the mass activity can reach 0.9A·mg Pt -1 And above, which is more than 4 times that of the popular platinum-carbon catalyst on the market. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a process flow chart of the preparation of the Pt-Cu / C catalyst of Example 1 of the present invention.

[0014] Figure 2 This is the CV graph of the Pt-Cu / C catalyst prepared in Example 1 of the present invention under a nitrogen atmosphere.

[0015] Figure 3 This is the LSV diagram of the Pt-Cu / C catalyst prepared in Example 1 of the present invention under an oxygen atmosphere.

[0016] Figure 4 This is a transmission electron microscopy image of the Pt-Cu / C catalyst prepared in Example 1 of the present invention.

[0017] Figure 5 This is the XRD pattern of the Pt-Cu / C catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0019] The process flow chart of the embodiment of the present invention is as follows Figure 1 shown.

[0020] Example 1

[0021] First, weigh 50 mg ECP600JD, 46.5 mg Cu(NO 3 ) 2 ·3H 2 O in a 100 ml beaker. Then add 30 ml of deionized water to the beaker and stir at 400 rpm for 4 hours. Add 15 g / L NaOH aqueous solution to adjust the pH of the mixed solution to 11, add 12 mg of hydrazine hydrate, turn on the water bath and control the temperature to 50 ° C, and keep warm for 20 minutes. After the reaction is completed, filter, wash with hot water and dry to obtain carbon-supported nano-copper particles.

[0022] Weigh 376.4 mg of a 10% platinum nitrate solution into a 100 ml beaker, then add 30 ml of deionized water, and adjust the pH of the platinum solution to 6.0 with a 40 g / l sodium hydroxide solution. Add 61.5 mg of carbon-supported nano-copper particles to the platinum-containing solution, stir at 400 rpm for 4 hours, transfer the mixed solution to a reactor, add 35.6 mg of sodium nitrite to the mixed solution, and adjust the pH of the solution to 6.0 with a 40 g / l sodium hydroxide solution again; use argon to drive out all the oxygen in the reactor, control the reactor temperature to 90 ° C, stir at 250 rpm, keep warm for 90 minutes, and then pass H 2 , and the hydrogen partial pressure in the reactor was controlled to be 0.5 MPa. After the reaction was completed, argon was used to drive out the hydrogen in the reactor, filtered and separated, washed with alcohol, and dried to obtain a carbon-supported core-shell structure PtCu catalyst.

[0023] The carbon-supported platinum-copper alloy catalyst prepared in this example was subjected to a redox test using a three-electrode system: + / H2 As reference electrode, platinum wire as counter electrode, electrolyte is 0.1M HClO 4 The purity of the nitrogen and oxygen used in the test is not less than 99.99%. The specific electrochemical test results are shown in Table 1. The LSV graph of the Pt-Cu / C catalyst prepared in Example 1 under a nitrogen atmosphere, the CV graph under an oxygen atmosphere, the transmission electron microscope graph and the XRD graph are shown in Table 1. Figure 2 , Figure 3 , Figure 4 , Figure 5 shown.

[0024] Example 2

[0025] First, weigh 0.5g EC600JD, 482mg Cu(SO 4 ) 2 ·5H 2 O in a 500ml beaker. Then add 300ml deionized water to the beaker and stir at 400rpm for 4h. Add 15g / L NaOH aqueous solution to adjust the pH of the mixed solution to 10, add 0.24g hydrazine hydrate, turn on the water bath, control the reaction temperature to 60℃, and keep warm for 25min. Then filter it, wash it with hot water at 80℃, and dry it.

[0026] Weigh 3.76g of platinum nitrate solution with a platinum mass concentration of 10%, add it to a 500ml beaker, then add 300ml of deionized water, and adjust the pH of the platinum solution to 4.0 with 40g / l sodium hydroxide solution. Add 0.62g of carbon-supported nano-copper particles, stir at 400rpm for 4h, transfer the mixed solution to a reactor, add 0.37g of sodium nitrite to the mixed solution, and adjust the pH of the solution to 8.0 with 40g / l sodium hydroxide solution again; then use argon to drive out the oxygen in the reactor, set the reactor temperature to 100℃, stir at 300rpm, keep warm for 100min, and then pass H 2 , the hydrogen partial pressure in the reactor was controlled to be 0.75 MPa. After the reaction was completed, argon was used to drive out the hydrogen in the reactor, filtered and separated, washed with ethanol and dried to obtain a carbon-supported core-shell structure PtCu catalyst.

[0027] The electrochemical test method is the same as that in Example 1. The specific electrochemical test results are shown in Table 1.

[0028] Example 3

[0029] First, weigh 50 mg XC-72, 93.13 mg Cu(NO 3 ) 2 ·3H 2O in a 100ml beaker. Then add 30ml of deionized water to the beaker and stir at 400rpm for 4h. Add 15g / L NaOH aqueous solution to adjust the pH of the mixed solution to 11, add 30mg of hydrazine hydrate, turn on the water bath and set the temperature to 65℃. After the temperature rises to 65℃, keep it warm for 35min. Then filter it, wash it with hot water at 80℃, and dry it.

[0030] Weigh 252.5 mg of 10% platinum nitrate solution into a 100 ml beaker, then add 30 ml of deionized water, and adjust the pH of the platinum solution to 2.0 with 40 g / l sodium hydroxide solution. Add 74 mg of carbon-supported nano-copper particles, stir at 400 rpm for 4 hours, transfer the mixed solution to a reactor, add 39 mg of EDTA-2Na to the mixed solution, and adjust the pH of the solution to 5.5 with 40 g / l sodium hydroxide solution again; then use argon to drive out oxygen in the reactor, control the reactor temperature to 105 ° C, stir at 250 rpm, keep warm for 90 minutes, and then pass H 2 , and the hydrogen partial pressure in the reactor was controlled to be 0.45 MPa. After the reaction was completed, argon was used to drive out the hydrogen in the reactor, filtered and separated, washed with ethanol, and dried to obtain a carbon-supported core-shell structure PtCu 3 catalyst.

[0031] The electrochemical test method is the same as that in Example 1. The specific electrochemical test results are shown in Table 1.

[0032] Comparative Example 1

[0033] Example 3 was repeated, except that the reducing agent in step A was potassium borohydride.

[0034] Comparative Example 2

[0035] Example 3 was repeated, except that the reducing agent in step A was ascorbic acid.

[0036] Comparative Example 3

[0037] Example 3 was repeated, except that the pH of the soaking step B was 1.

[0038] Comparative Example 4

[0039] Example 3 was repeated, except that the pH of the soaking step B was 10.

[0040] Comparative Example 5

[0041] Example 3 was repeated, except that no complexing agent was added in step B.

[0042] The electrochemical test method is the same as that in Example 1. The specific electrochemical test results are shown in Table 1.

[0043] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

[0044] Table 1

[0045]

Claims

1. A method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell, characterized in that: The following steps are involved: A. Preparation of Carbon-Supported Nanocopper The copper salt is completely dissolved in pure water, and the concentration of copper in the solution is controlled to be 0.1-1.5 g / L. A carbon carrier is then added to the above solution, and the ratio of the mass of the carbon carrier to the mass of copper is controlled to be 1.5-4.6:

1. After stirring and impregnating for 3-6 hours, a copper-containing precursor mixed solution is obtained. A sodium hydroxide solution with a concentration of 15 to 20 g / L is added dropwise to a mixed solution containing a copper precursor, the pH of the mixed solution is adjusted to 9 to 13, a reducing agent is added according to a mass ratio of the reducing agent to copper in the mixed solution of 0.8 to 2.5:1, the temperature is increased to 50 to 70°C, the reaction is carried out for 15 to 75 minutes, and the mixture is filtered and dried to obtain carbon-supported nano-copper particles. B. Preparation of Carbon-Supported Platinum-Copper Alloy Catalyst A platinum solution with a platinum concentration of 0.45 to 1.75 g / L is prepared, and a sodium hydroxide solution with a concentration of 20 to 40 g / L is used to adjust the pH of the platinum solution to 2.0 to 8.0, and then the carbon-supported nano-copper particles are added to the platinum solution to obtain a platinum-containing mixed solution, and the molar ratio of Cu and Pt in the platinum-containing mixed solution is controlled to be 1 to 3:1, and the mixture is stirred and impregnated for 3 to 11 hours. The platinum-containing mixed solution is placed in a reactor, and a ligand is added to the mixed solution, and the concentration of the ligand in the solution is controlled to be 0.1 g / L to 1.5 g / L, and the pH of the platinum-containing mixed solution is adjusted to 2.0 to 8.0 using a sodium hydroxide solution with a concentration of 20 to 40 g / L. The reaction mixture is adjusted to 5.0-8.0; then, argon is introduced into the reactor to drive out all the oxygen in the reactor, and the temperature is raised to 70-110° C., and hydrogen is introduced into the reactor to control the hydrogen partial pressure in the reactor to be 0.45-1.0 MPa, and the solution is stirred at a rate of 150-350 rpm for 60-120 min, and then the heating and stirring are stopped. When the temperature in the reactor drops below 50° C., the introduction of hydrogen is stopped and argon is introduced into the reactor to replace the hydrogen. When the hydrogen is completely replaced, the solid-liquid separation is performed, and the catalyst is washed with ethanol and dried to obtain a carbon-supported core-shell structure platinum-copper alloy catalyst.

2. The method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell according to claim 1, characterized in that: The copper salt is at least one of copper nitrate trihydrate and copper sulfate pentahydrate.

3. The method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell according to claim 1, characterized in that: The platinum salt is platinum nitrate.

4. The method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell according to claim 1, characterized in that: The carbon carrier is at least one of ECP600JD, EC600JD and XC-72.

5. The method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell according to claim 1 is characterized in that: The reducing agent is hydrazine hydrate.

6. The method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell according to claim 1, characterized in that: The ligand is at least one of EDTA-2Na and sodium nitrite.

7. The method for preparing a carbon-supported core-shell structured platinum-copper alloy catalyst for a fuel cell according to claim 1, characterized in that: The purity of the hydrogen is not less than 99.99%; the purity of the argon is not less than 99.99%.

Citation Information

Patent Citations

  • Carbon-carrying shell type copper-platinum catalyst for fuel cell and preparation method thereof

    CN102088091A

  • Preparation method of carbon-supported core-shell structure platinum-based catalyst for fuel cell

    CN113594473A

  • Biochar coupled copper catalyst and preparation method and application thereof

    CN115770572A

  • Preparation method of platinum-carbon catalyst for proton exchange membrane fuel cell and platinum-carbon catalyst

    CN118630240A

  • Preparation method of carbon-supported core-shell structure platinum-nickel catalyst for proton exchange membrane fuel cell

    CN118659001A